Manajemen Masjid Al-Munir Dalam Pengembangan Dakwah Islam Bagi Masyarakat Di Kabupaten Malang - Wahyudi Widodo (Journal on Education, 2024)
This study aims to determine the process of mosque management in the development of Islamic da'wah for the people of Malang Regency, as well as knowing about the challenges faced in the future. This research methodology uses qualitative or field research methods. The results obtained include: management of Al-Munir Mosque based on management functions, namely: Planning prepared by the Mosque and congregation management board in the form of da'wah activities that will be carried out over the next year, through deliberations planned matters that are the focus of Islamic da'wah activities at Al-Munir Mosque Malang. Organizing facilitates the distribution of members in holding duties, responsibilities. The implementation of Islamic da'wah activities in the mosque runs regularly and well. While the development of Islamic da'wah is in the form of recitation such as, routine recitation twice a week on Monday night and Thursday night, mosque youth recitation once a month, taklim assembly recitation after every shubuh, and recitation in Ramadan. The challenge is to invite as many people as possible to participate in existing activities so that the management also uses modern things, namely technology in order to make it easier for the people of Malang Regency to know